Inorganic powder, inorganic composition, and resin composition
Patent Information
- Application Number
- JP2023511120
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-03-30
- Filing Date
- 2022-03-24
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2042-03-24
AI Technical Summary
【0008】 本発明によれば、樹脂組成物中での凝集粒子の増大を防ぐことができる無機質粉末を提供することができる。
Smart Images

Figure 0007637761000001 
Figure 0007637761000002
Abstract
Description
[Technical field]
[0001] The present invention relates to an inorganic powder, an inorganic composition, and a resin composition. [Background technology]
[0002] In recent years, in response to the trend of miniaturization, weight reduction, and high performance of electronic devices, the miniaturization, thinning, and high density of semiconductor packages are accelerating. In addition, the mounting method thereof is becoming more and more dominated by surface mounting suitable for high density mounting on wiring boards and the like. As such, as semiconductor packages and their mounting methods progress, semiconductor encapsulation materials are also required to have high performance, particularly improved functions such as solder heat resistance, moisture resistance, low thermal expansion, mechanical properties, and electrical insulation. In order to meet these requirements, resin compositions are used in which inorganic powders such as metal oxides, particularly amorphous silica powder, are filled into resin. It is desirable to fill the inorganic powders filled into the semiconductor encapsulation material with a high amount of the resin from the viewpoint of improving solder heat resistance, moisture resistance, low thermal expansion, and mechanical strength.
[0003] However, semiconductor encapsulation materials highly filled with inorganic powder have a problem that the fluidity decreases as the filling rate increases, making it difficult to penetrate into the gap between the chip and the substrate, resulting in a very poor productivity. In order to suppress the decrease in fluidity, a method is known in which a small amount of fine powder or ultrafine powder with a particle size of less than 1 μm is added to a large powder with a particle size of about several tens of μm or a medium powder with a particle size of about several μm. Patent Document 1 describes a spherical inorganic powder having a maximum particle size of 6 μm or less, a frequency particle size distribution showing a maximum diameter at least in the particle size range of 1 to 3 μm, and the ratio of the mode diameter to the median diameter and the coefficient of variation of the frequency particle size distribution each falling within a specified range. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2003-221224 A Summary of the Invention [Problem to be solved by the invention]
[0005] Fine and ultrafine particles are prone to agglomeration when preparing semiconductor encapsulation materials because their particle size is very small. If the agglomerated particles increase, it can cause poor dispersion. In such cases, the yield of the semiconductor encapsulation material can decrease and the semiconductor can become defective or short-circuited in the final product.
[0006] An object of the present invention is to provide an inorganic powder capable of preventing an increase in agglomerated particles in a resin composition. [Means for solving the problem]
[0007] The present inventors have conducted intensive research, thinking that it may be possible to prevent an increase in aggregated particles while preventing a decrease in fluidity by controlling the number and height of peaks in a frequency particle size distribution diagram. Surprisingly, they have found that an inorganic powder having a volume-based cumulative 50% diameter within a predetermined range, at least two peaks in a frequency particle size distribution diagram, and the half-width of the peak located on the smaller particle size side is less than a predetermined value, can reduce the aggregation in a resin composition while maintaining the excellent fluidity of the resin composition. The inorganic powder designed in this way is a novel powder that has never been seen before. The present invention has the following embodiments. [1] Volume-based cumulative 50% diameter D 50 The inorganic powder has a particle size distribution of 1.2 to 2.8 μm, and includes at least a first peak and a second peak located on the larger particle size side than the first peak in a volume-based frequency particle size distribution, and the half width of the first peak is less than 0.5 μm. [2] BET specific surface area is 15-24m 2 / g. The inorganic powder according to [1]. [3] The inorganic powder according to [1] or [2], wherein the half width of the second peak is 2.2 to 3.2 μm. [4] An inorganic composition comprising an inorganic powder according to any one of [1] to [3]. [5] A resin composition comprising the inorganic powder according to any one of [1] to [3] and a resin. [6] The resin composition according to [5], which is a liquid encapsulant. Effect of the Invention
[0008] According to the present invention, it is possible to provide an inorganic powder capable of preventing an increase in agglomerated particles in a resin composition. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] An embodiment of the present invention will be described in detail below. The present invention is not limited to the following embodiment, and can be implemented by making appropriate modifications within a range that does not impair the effects of the present invention. In this specification, the expression "X to Y" regarding a numerical range means not less than X and not more than Y.
[0010] [Inorganic powder] The inorganic powder according to the present embodiment has a volume-based cumulative 50% diameter D 50 The inorganic powder has a volume-based cumulative 50% diameter D of 1.2 to 2.8 μm, and in the volume-based frequency particle size distribution, at least a first peak and a second peak located on the larger particle size (particle size) side than the first peak are included, and the half-value width of the first peak is less than 0.5 μm. 50 Since the diameter of the first peak is 1.2 to 2.8 μm and the half width of the first peak is less than 0.5 μm, it is possible to prevent an increase in aggregated particles in the resin composition. In addition, when the inorganic powder is mixed with a large inorganic powder having a particle size of about several tens of μm or a medium inorganic powder having a particle size of about several μm, it is possible to prevent an increase in aggregated particles in the resin composition. The inorganic powder designed in this way is a novel inorganic powder that has never been designed before, and has the above-mentioned volume-based cumulative 50% diameter D 50 The characteristics of the half width of the first peak are very important factors in achieving both high fluidity of the resin composition and low aggregation of the inorganic powder in the resin composition.
[0011] (Volume-based cumulative diameter) "Volume-based cumulative 50% diameter D 50" (also called "median size") is the particle size at which the cumulative value corresponds to 50% in the cumulative particle size distribution on a volume basis measured by the laser diffraction scattering method (refractive index: 1.50). The cumulative particle size distribution is expressed by a distribution curve with the particle size (μm) on the horizontal axis and the cumulative value (%) on the vertical axis. The cumulative particle size distribution on a volume basis measured by the laser diffraction scattering method (refractive index: 1.50) is measured using a laser diffraction scattering type particle size distribution analyzer (Beckman Coulter, "LS-230"), using water (refractive index: 1.33) as the solvent, and dispersing the particles for 2 minutes as a pretreatment by applying 200W output using Tommy Seiko's "Ultrasonic Generator UD-200 (with ultra-micro tip TP-040 attached)".
[0012] Volume based cumulative 50% diameter D 50 In one embodiment, the volume-based cumulative 50% diameter D 50 can be 1.5 to 2.5 μm. Volume based cumulative 50% diameter D 50 The adjustment of can be made, for example, by adjusting the size and classification of the raw material powder. For example, in addition to adjusting the particle size of the raw material powder, classification (using a sieve classification or an air classifier) after spheroidization can be performed to adjust the volume-based cumulative 50% diameter D 50 can be adjusted to.
[0013] Inorganic powder is a volume-based cumulative 10% diameter D 10 is preferably 0.1 to 0.3 μm, and more preferably 0.2 to 0.3 μm. 10 By setting the diameter of the particles to 0.1 to 0.3 μm, the particles can easily enter the gaps between large and medium-sized particles, allowing the particles to be packed more densely. Also, the amount of agglomerates can be reduced. 10 If it is too small, the flowability and moldability are easily impaired. Inorganic powder is a volume-based cumulative 25% diameter D 25is preferably 0.1 to 2.0 μm, more preferably 0.1 to 1.0 μm, and further preferably 0.1 to 0.8 μm. 25 By adjusting the diameter D, the number of particles contained in the first peak is further optimized, and the effect of the present invention is further enhanced. 25 can be between 0.4 and 1.7. Inorganic powder is a volume-based cumulative 90% diameter D 90 The volume-based cumulative 90% diameter D is preferably 2.8 to 4.5 μm, more preferably 2.8 to 4.0 μm, and further preferably 3.2 to 4.0 μm. 90 By setting the diameter of the particles to 2.8 to 4.5 μm, the filling property can be improved and the fluidity can be significantly improved. 90 can be between 3.1 and 4.3. Inorganic powder is a volume-based cumulative 100% diameter D 100 The volume-based cumulative 100% diameter D is preferably 6.0 to 8.5 μm, more preferably more than 6.0 μm and not more than 8.0 μm, and further preferably 6.2 to 8.0 μm. 100 By setting the diameter D to 6.0 to 8.5 μm, the gaps between the particles can be filled and more suitable fluidity can be obtained. 100 can be between 6.8 and 8.1. Volume based cumulative 10% diameter D 10 , volume-based cumulative 25% diameter D 25 , volume-based cumulative 90% diameter D 90 and volume-based cumulative 100% diameter D 100 are particle sizes at which the cumulative value is 10%, 25%, 90%, or 100% in the volume-based cumulative particle size distribution measured by a laser diffraction / scattering particle size distribution analyzer. The measurement method is the volume-based cumulative 50% diameter D 50 The adjustment method is the same as the volume-based cumulative 50% diameter D 50 In other words, in addition to adjusting the particle size of the raw powder, it is possible to obtain a 10% cumulative diameter D based on a specified volume by classifying (by sieve classification or air classifier) after spheroidization. 10 , volume-based cumulative 25% diameter D25 , volume-based cumulative 90% diameter D 90 and volume-based cumulative 100% diameter D 100 can be adjusted to.
[0014] (Frequency particle size distribution) The "volume-based frequency particle size distribution" is measured by the laser diffraction scattering method (refractive index: 1.50) and is represented by a distribution curve with the particle size (μm) on the horizontal axis and the volume-based frequency (%) on the vertical axis. The volume-based frequency particle size distribution measured by the laser diffraction scattering method (refractive index: 1.50) is measured using a laser diffraction scattering particle size distribution analyzer (Beckman Coulter, "LS-230"), water (refractive index: 1.33) as the solvent, and a dispersion treatment is performed for 2 minutes as a pretreatment by applying 200W output using Tommy Seiko's "Ultrasonic Generator UD-200 (with ultra-micro tip TP-040 attached)".
[0015] The inorganic powder has a first peak and a second peak located on the larger particle size side than the first peak in the volume-based frequency particle size distribution. That is, the inorganic powder has at least two peaks including the first peak and the second peak in the volume-based frequency particle size distribution. Of the two peaks, the peak located on the smaller particle size side is the first peak, and the peak located on the larger particle size side is the second peak.
[0016] The term "peak" as used herein means a mountain-shaped curve having a boundary (maximum value) where the slope of the curve changes from positive to negative in the volume-based frequency particle size distribution. In this specification, the term "peak" does not include a shoulder (a portion where a bulge or step is formed in the middle of the slope of the curve constituting one peak). Each peak may have a shoulder, but from the viewpoint of filling the resin between the particles, each peak preferably does not have a shoulder.
[0017] The inorganic powder may have only the first and second peaks in the volume-based frequency particle size distribution, or may have one or more other peaks. The other one or more peaks may be present between the first and second peaks, may be present on the side with a smaller particle size than the first peak, or may be present on the side with a larger particle size than the second peak. When three or more peaks are present, any two peaks are defined as the first peak and the second peak. If the frequency at both ends of the first and second peaks is not 0, the minimum value is taken as the start or end point of the peak.
[0018] In one embodiment, the first peak and the second peak may be adjacent (i.e., there are no other peaks between the first peak and the second peak), while in another embodiment, there may be one or more peaks between the first peak and the second peak.
[0019] The half width of the first peak is less than 0.5 μm, preferably 0.45 μm or less, and more preferably 0.4 μm or less. In one embodiment, the half width of the first peak is 0.1 μm or more and less than 0.5 μm, preferably 0.1 μm or more and 0.45 μm or less, and more preferably 0.1 μm or more and 0.4 μm or less. In one embodiment, the half width of the first peak may be 0.2 μm or more and less than 0.5 μm, preferably 0.2 μm or more and 0.45 μm or less, and more preferably 0.2 μm or more and 0.4 μm or less.
[0020] In this specification, the term "half-value width" refers to the difference in particle size between two points having a frequency that is half the frequency of the maximum value in a volume-based frequency particle size distribution measured by a laser diffraction scattering method (refractive index: 1.50). The half-width of the first peak can be adjusted by adjusting the size of the raw material powder or by adjusting the melting temperature (flame temperature) when the raw material powder is converted into fine spherical powder in a high-temperature flame. The manufacturing method will be described later.
[0021] The half width of the second peak is preferably 2.2 to 3.2 μm, more preferably 2.3 to 3.2 μm, further preferably 2.3 to 3.2 μm, and particularly preferably 2.4 to 3.1 μm. By setting the half width of the second peak to 2.2 to 3.2 μm, appropriate fluidity can be easily maintained. The half-width of the second peak can be adjusted by adjusting the size of the raw material powder or by adjusting the temperature at which the raw material powder is collected after being converted into fine spherical powder in a high-temperature flame. The manufacturing method will be described later.
[0022] The first peak and the second peak each have a maximum value (the boundary where the slope of the curve changes from positive to negative). In one embodiment, the inorganic powder may have at least two peaks, each having a maximum value, preferably in a particle size range of 4.0 μm or less, more preferably at least two peaks, each having a maximum value, in a particle size range of 3.5 μm or less, and even more preferably at least two peaks, each having a maximum value, in a particle size range of 3.0 μm or less. By having at least two peaks, each having a maximum value, in a particle size range of 4.0 μm or less, a resin composition with better fluidity can be obtained. In other words, in one embodiment, the first peak and the second peak can both have a maximum value in a particle size range of preferably 4.0 μm or less, more preferably in a particle size range of 3.5 μm or less, and even more preferably in a particle size range of 3.0 μm or less.
[0023] The first peak preferably has a maximum value in a particle size range of 0.1 to 1.0 μm, more preferably has a maximum value in a particle size range of 0.1 μm or more and less than 1.0 μm, even more preferably has a maximum value in a particle size range of 0.1 to less than 0.8 μm, and particularly preferably has a maximum value in a particle size range of 0.1 to 0.5 μm.
[0024] The second peak preferably has a maximum value in a particle size range of more than 1.0 μm to 4.0 μm, more preferably has a maximum value in a particle size range of 1.5 to 3.5 μm, even more preferably has a maximum value in a particle size range of 1.5 to 3.0 μm, and particularly preferably has a maximum value in a particle size range of 2.0 to 3.0 μm.
[0025] In terms of further reducing the aggregation tendency, it is preferable that the frequency value (%) at the maximum value of the second peak is greater than the frequency value (%) at the maximum value of the first peak.
[0026] The frequency at the maximum value (maximum diameter) of the first peak is preferably 0.5 to 5.0%, more preferably 0.5 to 3.0%, even more preferably 0.5 to 2.8%, still more preferably 0.7 to 2.7%, and particularly preferably 0.9 to 2.5%. By setting the frequency at the maximum value of the first peak to 0.5 to 5.0%, the ratio of the frequency at the maximum value of the first peak to the frequency at the maximum value of the second peak can be easily adjusted to a predetermined range.
[0027] The frequency at the maximum value of the second peak is 3.5 to 9.0%, more preferably 4.0 to 8.5%, further preferably 4.5 to 8.0%, and particularly preferably 4.8 to 7.6%. By setting the frequency at the maximum value of the second peak to 3.5 to 9.0%, the ratio of the frequency at the maximum value of the first peak to the frequency at the maximum value of the second peak can be easily adjusted to a predetermined range.
[0028] (Inorganic powder) The inorganic powder may be a metal oxide powder. The metal oxide powder may be silica (SiO 2 ), Alumina (Al 2 O 3 ), titania (TiO 2Examples of inorganic powders include silica (calcia), magnesia (MgO), and the like. The inorganic powder preferably contains one or more metal oxide powders selected from these, and more preferably contains silica. The inorganic powder is preferably a spherical inorganic powder, and more preferably spherical silica. From the viewpoints of bringing the thermal expansion coefficients of the semiconductor chip and the liquid encapsulant closer to each other, solder heat resistance, moisture resistance, and low wear of the mold, amorphous silica produced by a method of melting crystalline silica at high temperature is preferred.
[0029] In order to further reduce agglomeration, the inorganic powder should have a specific surface area of 10 to 30 m2 as measured by the BET method. 2 / g, and 15 to 24m 2 / g is more preferable. The specific surface area can be measured by the BET method using a specific surface area measuring device. Here, the measurement was performed using a "Macsorb HM model-1208" (manufactured by Mountec Co., Ltd.).
[0030] (Method of manufacturing inorganic powder) The inorganic powder having the above-mentioned predetermined physical properties can be produced, for example, by crushing and classifying a commercially available ore as necessary, and then feeding it into a high-temperature flame to convert it into a fine spherical powder. This production method, for example, has the following steps. (i) optionally crushing and classifying the ore to obtain an ore powder (corresponding to an example of a raw material powder); (ii) feeding the ore powder into a high-temperature flame in a reaction vessel to form a fine spherical powder (molten powder); and (iii) optionally classifying and collecting the fine spherical powder;
[0031] Process (i) The ore used in step (i) is preferably high purity (e.g., 95% or more). Examples of the ore include silica sand, silica stone, titanium ore, magnesium ore, calcium ore, etc., and it is preferable to use one or more selected from these, and it is more preferable to use silica stone. The ore is pulverized using a pulverizer such as a vibration mill or a ball mill, so that an ore powder having a desired average particle size can be appropriately selected. The raw powder has a particle size (volume-based cumulative 50% diameter D 50 ) is preferably 3.0 to 7.0 μm, and more preferably 4.5 to 5.5 μm. A mixture of multiple types of raw material powders having different particle sizes can also be used.
[0032] Process (ii) In step (ii), the ore powder obtained in step (i) is injected into a high-temperature flame formed by a combustible gas and a combustion supporting gas using a burner, melted and spheroidized at a temperature above the melting point of the ore powder (for example, a temperature of 1800°C or higher in the case of silica (quartz stone)), and classified and collected while cooling to obtain a spheroidized powder (fine spherical powder). As the combustible gas, hydrocarbon gases such as acetylene, ethylene, methane, ethane, propane, and butane; hydrogen; gaseous fuels such as LPG and LNG; and liquid fuels such as kerosene and heavy oil; can be used. As the combustion supporting gas, oxygen, oxygen-rich cooling gas, and air can be used.
[0033] The half width of the first peak can be adjusted by adjusting the melting temperature. For example, lowering the melting temperature reduces the half width of the first peak. The melting temperature (flame temperature) is 1800 to 2200°C, more preferably 1900 to 2100°C, and further preferably 1950 to 2100°C. The melting temperature can be adjusted, for example, by the amount of gas and the amount of oxygen.
[0034] Process (iii) In step (iii), the fine spherical powder obtained in step (ii) is further classified and collected by a cyclone, sieving operation, etc., if necessary. The half-width of the second peak can be adjusted by adjusting the powder collection temperature (the temperature of the bag filter when collecting the powder). For example, lowering the powder collection temperature reduces the half-width of the second peak. The BET specific surface area can be adjusted by adjusting the powder collection temperature. For example, lowering the powder collection temperature increases the BET specific surface area. The powder collection temperature is preferably more than 100°C and less than 300°C, more preferably 120 to 290°C, even more preferably 150 to 280°C, and even more preferably 170 to 250°C.
[0035] (Application) The inorganic powder according to the present embodiment can be used for various applications. For example, it can be used for manufacturing materials such as semiconductor encapsulants. In particular, it can provide a resin composition with excellent flowability and prevent an increase in aggregated particles in the resin composition, so it can be preferably used for manufacturing semiconductor encapsulants for electronic devices.
[0036] [Inorganic composition] The inorganic composition according to this embodiment contains the inorganic powder according to the above embodiment. Hereinafter, the inorganic powder according to the above embodiment is also referred to as "inorganic powder (P1)". The type and properties of the inorganic powder (P1) are as described above, and therefore will not be described here. The inorganic powder (P1) has a particle size (volume-based cumulative 50% diameter D 50 Since the inorganic powder (P1) is composed of very fine particles with a diameter of 1.2 to 2.8 μm, a small amount of this inorganic powder (P1) can be added to a large-particle diameter powder with a diameter of about several tens of μm or a medium-particle diameter powder with a diameter of about several μm to produce an inorganic composition, which can provide a resin composition with excellent fluidity even when the resin is highly filled with inorganic substances (filled at a high content). In addition, the inorganic powder (P1) has a volume-based cumulative 50% diameter D 50 Since the half width of the first peak is less than 0.5 μm in addition to the wavelength of 1.2 to 2.8 μm, an increase in aggregated particles in the resin composition can be prevented.
[0037] In one embodiment, the mineral composition further has a volume-based cumulative 50% diameter D 50 Inorganic powder (P2) having a volume-based cumulative 50% diameter D 50The resin composition may contain an inorganic powder (P3) having a particle size of 3 μm or more and less than 10 μm (preferably 3 μm or more and 8 μm or less, more preferably 4 μm or more and 6 μm or less). By containing such a large particle size inorganic powder (P2) and / or a medium particle size inorganic powder (P3), the solder heat resistance, moisture resistance, low thermal expansion property, and mechanical strength of the resin composition can be improved.
[0038] The types (compound types) of the inorganic powder (P2) and the inorganic powder (P3) are not particularly limited and can be selected from those exemplified as the inorganic powder (P1) according to the above embodiment. The types of the inorganic powder (P2) and the inorganic powder (P3) may be the same as or different from the inorganic powder (P1), independently of each other.
[0039] The content of the inorganic powder (P1) in the inorganic composition is preferably 0.1 to 30 mass%, more preferably 1 to 20 mass%, and even more preferably 3 to 20 mass%. By making the content of the inorganic powder in the inorganic composition 0.1 to 30 mass%, it is possible to provide a resin composition having excellent fluidity even when the inorganic composition is highly filled in the resin.
[0040] The content of the inorganic powder (P2) and / or the inorganic powder (P3) in the inorganic composition is preferably 70 to 99.9 mass %, more preferably 80 to 99 mass %, and even more preferably 80 to 97 mass % in total.
[0041] (Manufacturing method) The method for producing the inorganic composition is not particularly limited, and the inorganic composition can be obtained by mixing the inorganic powders by dry blending or the like using a known device.
[0042] (Application) The inorganic composition according to the present embodiment can be used for various applications. For example, it can be used for manufacturing materials such as semiconductor encapsulants. In particular, it can provide a resin composition with excellent flowability and prevent an increase in aggregated particles in the resin composition, so it can be preferably used for manufacturing semiconductor encapsulants for electronic devices.
[0043] [Resin composition] The resin composition according to the present embodiment contains a resin and the inorganic powder (P1) described above. Since the resin contains the inorganic powder (P1), it has excellent fluidity even when the resin is highly filled with inorganic substances. The type and physical properties of the inorganic powder (P1) are as described above, so they will not be described here.
[0044] The content of the inorganic powder (P1) in the resin composition is preferably 0.1 to 30 mass%, more preferably 1 to 20 mass%, and even more preferably 3 to 17 mass%. By making the content of the inorganic powder in the resin composition 0.1 to 30 mass%, it is possible to realize excellent fluidity even when the resin is highly filled with the inorganic substance.
[0045] In one embodiment, the resin composition further contains the inorganic powder (P2) and / or the inorganic powder (P3). The types and properties of the inorganic powder (P2) and the inorganic powder (P3) are as described above, and therefore will not be described here.
[0046] The content of the inorganic powder (P2) and / or the inorganic powder (P3) in the resin composition is preferably 65 to 95 mass%, more preferably 70 to 90 mass%, and even more preferably 70 to 87 mass%. By making the total content of the inorganic powders (P1) to (P3) in the resin composition 65 to 95 mass%, the resin is highly filled with the inorganic powders, and the solder heat resistance, moisture resistance, low thermal expansion, and mechanical strength of the resin composition can be improved.
[0047] (resin) Examples of the resin include epoxy resin, silicone resin, phenol resin, melamine resin, urea resin, unsaturated polyester, fluororesin, polyimide, polyamideimide, polyetherimide, and other polyimides, polybutylene terephthalate, polyethylene terephthalate, and other polyesters, polyphenylene sulfide, wholly aromatic polyester, polysulfone, liquid crystal polymer, polyethersulfone, polycarbonate, maleimide-modified resin, ABS resin, AAS (acrylonitrile-acrylic rubber-styrene) resin, AES (acrylonitrile-ethylene-propylene-diene rubber-styrene) resin, etc. The resin preferably contains one or more selected from these, and more preferably contains an epoxy resin.
[0048] The epoxy resin is not particularly limited, and examples thereof include phenol novolac type epoxy resins, orthocresol novolac type epoxy resins, epoxidized novolac resins of phenols and aldehydes, glycidyl ethers of bisphenol A, bisphenol F, bisphenol S, and the like, glycidyl ester acid epoxy resins obtained by reacting polybasic acids such as phthalic acid and dimer acid with epochlorohydrin, linear aliphatic epoxy resins, alicyclic epoxy resins, heterocyclic epoxy resins, alkyl-modified polyfunctional epoxy resins, β-naphthol novolac type epoxy resins, 1,6-dihydroxynaphthalene type epoxy resins, 2,7-dihydroxynaphthalene type epoxy resins, bishydroxybiphenyl type epoxy resins, and further epoxy resins into which halogens such as bromine have been introduced to impart flame retardancy.
[0049] The resin preferably contains one or more epoxy resins selected from these, and more preferably contains an epoxy resin that is liquid at room temperature. Among these, the resin particularly preferably contains one or more epoxy resins selected from bisphenol-type epoxy resins such as bisphenol A-type epoxy resins and bisphenol F-type epoxy resins, and alicyclic epoxy resins.
[0050] The content of the resin in the resin composition is preferably 1 to 10 mass %, more preferably 2 to 9 mass %, further preferably 3 to 8 mass %, and particularly preferably 4 to 6 mass %.
[0051] (hardening agent) When the resin composition contains an epoxy resin, it is preferable that the resin composition further contains a curing agent. Examples of the curing agent include a novolac type resin obtained by reacting one or more mixtures selected from the group consisting of phenol, cresol, xylenol, resorcinol, chlorophenol, t-butylphenol, nonylphenol, isopropylphenol, octylphenol, etc. with formaldehyde, paraformaldehyde, or paraxylene under an oxidation catalyst, a polyparahydroxystyrene resin, a bisphenol compound such as bisphenol A or bisphenol S, a trifunctional phenol such as pyrogallol or phloroglucinol, an acid anhydride such as maleic anhydride, phthalic anhydride, or pyromellitic anhydride, and an aromatic amine such as metaphenylenediamine, diaminodiphenylmethane, or diaminodiphenylsulfone.
[0052] The content of the curing agent is preferably such that the hydroxyl equivalent (or acid anhydride equivalent) of the curing agent is 0.5 to 1.25 per 1 epoxy equivalent of the epoxy resin.
[0053] (Other additives) The resin composition may contain a curing accelerator, a release agent, a coupling agent, a colorant, etc., within the range not impairing the effects of the present invention. The curing accelerator is not particularly limited, and examples thereof include 1,8-diazabicyclo(5,4,0)undecene-7, triphenylphosphine, benzyldimethylamine, and 2-methylimidazole. Examples of the release agent include natural waxes, synthetic waxes, metal salts of straight-chain fatty acids, acid amides, esters, and paraffin. The coupling agent may be a silane coupling agent, such as epoxy silanes (gamma-glycidoxypropyltrimethoxysilane, beta-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, amino silanes (aminopropyltriethoxysilane, ureidopropyltriethoxysilane, N-phenylaminopropyltrimethoxysilane, etc.), hydrophobic silane compounds (phenyltrimethoxysilane, methyltrimethoxysilane, octadecyltrimethoxysilane, etc.), and mercaptosilanes.
[0054] (Manufacturing method) The method for producing the resin composition is not particularly limited, and the resin composition can be produced by stirring, dissolving, mixing, and dispersing a predetermined amount of each material. The apparatus for mixing, stirring, dispersing, etc. of the mixture is not particularly limited, but a mortar and pestle machine equipped with a stirring and heating device, a three-roll mill, a ball mill, a planetary mixer, etc. can be used. These apparatuses may also be used in appropriate combination.
[0055] (Application) The resin composition according to the present embodiment can be used for manufacturing a semiconductor encapsulant. In particular, since the resin composition has excellent flowability and the inorganic powder is less likely to aggregate, it can be preferably used as a semiconductor encapsulant (liquid encapsulant) for electronic devices. EXAMPLES
[0056] The present invention will be described in more detail below with reference to examples, but the interpretation of the present invention is not limited to these examples.
[0057] [Production Example 1] Natural silica with a purity of 90% or more is crushed and classified into silica raw powder (50% cumulative diameter by volume D) using a vertical furnace with a burner installed at the top and a collection system (cyclone and bag filter). 50The silica particles (fine particle diameter: 4.8μm) were fed into a high-temperature flame formed by the combustion of LPG and oxygen, and melted and spheroidized to obtain spherical amorphous silica powder. The particles were classified using a sieve classifier or an air classifier to obtain spherical amorphous silica powder having the volume-based cumulative diameter and the maximum value of the peak in the frequency particle size distribution shown in Table 1. The powder collection temperature was set to 230℃.
[0058] [Manufacturing Examples 2 to 5] A spherical amorphous silica powder was obtained in the same manner as in Example 1, except that the powder collection temperature was set as shown in Table 1.
[0059] [Comparative Manufacturing Examples 1, 3-5, 7-8] A spherical amorphous silica powder was obtained in the same manner as in Example 1, except that the flame temperature and powder collection temperature were as shown in Table 1.
[0060] [Comparative Manufacturing Example 2] Silica raw powder (volume basis cumulative 50% diameter D 50 The procedure of Production Example 1 was repeated except that a powder collection temperature as shown in Table 1 was used.
[0061] [Comparative Manufacturing Example 6] Volume based cumulative 50% diameter D 50 Silica powder with a diameter of 1.0 μm and a volume-based cumulative 50% diameter D 50 The silica powder having a particle size of 0.1 μm was mixed with a silica powder having a particle size of 0.5 μm in a mass ratio of 8:2 using a vertical mixer to obtain a silica powder (mixed powder).
[0062] [Comparative Manufacturing Example 9] Volume based cumulative 50% diameter D 50 The same procedure as in Production Example 1 was repeated except that silica powder having a diameter of 2.5 μm was used and the powder collection temperature was as shown in Table 1.
[0063] [measurement] (Volume based cumulative) The silica powders of Production Examples 1 to 5 and Comparative Production Examples 1 to 9 were dispersed using a laser diffraction scattering particle size distribution analyzer (manufactured by Beckman Coulter, "LS-230") with water (refractive index: 1.33) as a solvent for 2 minutes as a pretreatment, with an output of 200 W using an "ultrasonic generator UD-200 (with ultra-micro tip TP-040)" manufactured by Tommy Seiko Co., Ltd., to measure the cumulative particle size distribution measured by the laser diffraction scattering method (refractive index: 1.50). The cumulative 10% diameter D 10 , volume-based cumulative 25% diameter D 25 , volume-based cumulative 50% diameter D 50 , volume-based cumulative 90% diameter D 90 , and the volume-based cumulative 100% diameter D 100 The results are shown in Table 1.
[0064] (Frequency particle size distribution) The silica powders of Production Examples 1 to 5 and Comparative Production Examples 1 to 9 were dispersed using a laser diffraction scattering particle size distribution analyzer (manufactured by Beckman Coulter, "LS-230") with water (refractive index: 1.33) as the solvent for 2 minutes as pretreatment, with an output of 200 W using an "ultrasonic generator UD-200 (with ultra-micro tip TP-040)" manufactured by Tommy Seiko Co., Ltd., and the volume-based frequency particle size distribution measured by the laser diffraction scattering method (refractive index: 1.50) was measured, and the half-width of each peak was calculated. The results are shown in Table 1.
[0065] The spherical amorphous silica powders of Production Examples 1 to 5 have two peaks with maximum values in the particle size range of 3.0 μm or less. The two peaks are composed of a peak (first peak) with a maximum value in the vicinity of the 0.1 to 0.5 μm region and a peak (second peak) with a maximum value in the vicinity of the 2.0 to 3.0 μm region. The first and second peaks are adjacent to each other and neither has a shoulder. The frequency at the maximum value of the second peak is higher than the frequency at the maximum value of the first peak. The spherical amorphous silica powders of Production Examples 1 to 5 do not have a maximum value in the particle size range exceeding 3.0 μm, and do not have a frequency particle size distribution in the particle size range of 7.0 μm or more.
[0066] Between the first and second peaks, there is a boundary (minimum value) where the slope of the curve changes from negative to positive in the vicinity of the region of 0.5 to 1 μm. In detail, the spherical amorphous silica powder of Production Example 1 has a minimum value of particle size 0.7 μm and frequency 0.4%. The spherical amorphous silica powder of Production Example 2 has a minimum value of particle size 0.8 μm and frequency 1.6%. The spherical amorphous silica powder of Production Example 3 has a minimum value of particle size 0.6 μm and frequency 1.7%. The spherical amorphous silica powder of Production Example 4 has a minimum value of particle size 0.7 μm and frequency 0%.
[0067] [Table 1]
[0068] [Examples 1 to 11, Comparative Examples 1 to 11] In order to evaluate the properties of the resin compositions containing silica powder of Production Examples 1 to 5 and Comparative Production Examples 1 to 9, resin compositions were produced using the following materials. Resin: Biphenyl type epoxy resin (manufactured by Mitsubishi Chemical Corporation, "YH-4000HK") Hardener: Phenolic resin (manufactured by Meiwa Kasei Co., Ltd.) Curing accelerator: Triphenylphosphine Release Agent Silane coupling agent: epoxy silane (manufactured by Shin-Etsu Chemical Co., Ltd., "KBM-403")
[0069] The resin compositions were produced as follows: The silica powders of Production Examples 1 to 5 and Comparative Production Examples 1 to 9 and the above materials were mixed in the components and ratios shown in Table 2 using a rotation-revolution type planetary mixer (Awatori Rentaro AR-360M; manufactured by Thinky Corporation) at a rotation speed of 2000 rpm and a revolution speed of 600 rpm for 10 minutes, and then vacuum degassed to obtain resin compositions.
[0070] The flowability of the resulting resin composition and the state of aggregation of the silica powder in the resin composition were measured and evaluated by the following methods. The results are shown in Table 2. (Liquidity assessment) The spiral flow value of each resin composition was measured using a transfer molding machine equipped with a spiral flow measurement mold in accordance with EMMI-I-66 (Epoxy Molding Material Institute; Society of Plastics Industry). The transfer molding conditions were a mold temperature of 175° C., a molding pressure of 7.4 MPa, and a pressure holding time of 120 seconds. A larger value (preferably 115 cm or more) indicates better fluidity.
[0071] (Evaluation of agglomeration state: Measurement of the content of agglomerates with openings of 75 μm or more) 100g of silica was weighed and placed on a sieve with 75μm mesh. 1000mL of pure water was sieved through a shower nozzle for 30 seconds. The silica remaining on the sieve was collected in an evaporating dish and dried in a dryer, after which it was weighed and the percentage of the residue was calculated. The evaluation was made according to the following criteria: "Good" indicates that aggregation in the resin composition can be suppressed. 〇(Pass): 0.0%~2.0% △(Fail):2.0%~10% ×(Fail):10%~100%
[0072] [Table 2]
Claims
1. The volume-based cumulative 50% diameter D50 is 1.2 to 2.8 μm; In a volume-based frequency particle size distribution represented by a distribution curve with the horizontal axis being the particle diameter (μm) and the vertical axis being the volume-based frequency (%), the particle size distribution includes at least a first peak and a second peak located on the larger particle size side than the first peak, and the half width of the first peak is less than 0.5 μm, BET specific surface area: 15 to 24 m 2 / g of metal oxide powder.
2. 2. The metal oxide powder according to claim 1, wherein the half width of the second peak is 2.2 to 3.2 μm.
3. An inorganic composition comprising the metal oxide powder according to claim 1 or 2.
4. A resin composition comprising the metal oxide powder according to claim 1 or 2 and a resin.
5. The resin composition according to claim 4, which is a liquid encapsulant.
Citation Information
Patent Citations
Grinding method for wafer
CN109427573A
Production of hydroxystannate and flame retardant
JP1998297920A
Silica-containing resin composition and its precision molding
JP2003003074A
Spherical inorganic powder and use thereof
JP2003221224A
Glare-proof hard coat film
JP2006218798A